The Clergy of the Archdiocese of Lviv of the Latins in Aid of the Jewish Nation ... during the Years of the German Occupation from 1941–1944. An Outline of the Events - Grzegorz Chajko (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
During the German occupation, large numbers of Poles were actively involved in assisting the persecuted Jews. Among the Poles who extended help were also priests from the Archdiocese of Lviv of the Latins. This article addresses their assistance and protection of the many Jews who were being persecuted by the German Army. Certainly, it does not exhaust the subject, but constitutes some contribution to ongoing research. It is not an easy undertaking, since the sources are extremely scanty, and the search for any information is both a time and labor consuming occupation. Still, given the information gathered here, we are given an opportunity to discern a certain image of clergymen who unhesitatingly sacrificed themselves to save the lives of people who were followers of a different faith. Two priests laid down their lives in the process.